Sen dan Manajemen Dakwah Kajian Dakwah USTAD Syam di TIK TOK - wadi, Hamzanwadi Hamzan (Mudabbir: Jurnal Manajemen Dakwah, 2023)
The portrait of da'wah today is in line with technological developments. Where da'i can give da'wah through social media such as YouTube, Facebook, Instagram, and recently the coolest thing is the Tik Tok account. The existence of social media provides a variety of information that can be enjoyed by the public, both about economics, business, education, social matters, conflict issues, and especially about religion. Recently it went viral for a cleric who made the name of his congregation Al-Tiqtoqiyah on TikTok. He is Ustadz Syamsuddin Nur Makka or familiarly known as Ustadz Sam. Jama'ah Al-tiqtoqiyah was officially opened by Ustadz Syam on January 17 2021, in his post (@Syam_elmarusy). This research uses the Net Notrafi method which focuses on the art and management of Ustad Syam's preaching on his Tik Tok account. The research concluded that the art and management of Ustad Syam's preaching on the Tik Tok account presented a new term regarding da'wah media, namely the use of social media such as YouTube, Instagram, Facebook, Tik Tok and other social media as new media for carrying out da'wah. So that the da'wah movement carried out is always dynamic in accordance with current developments and according to the needs of society.